Analysis of inappropriate prescribing in elderly patients of the Swiss HIV Cohort Study reveals gender inequity. (5th December 2020) - Livio, Françoise; Deutschmann, Elisabeth; Moffa, Giusi; Rrustemi, Flamur; Stader, Felix; Elzi, Luigia; Braun, Dominique L; Calmy, Alexandra; Hachfeld, Anna; Cavassini, Matthias; Tarr, Philip E; Wissel, Kerstin; et al.
Abstract: Background: The extent of inappropriate prescribing observed in geriatric medicine has not been thoroughly evaluated in people ageing with HIV. We determined the prevalence of and risk factors for inappropriate prescribing in individuals aged ≥75 years enrolled in the Swiss HIV Cohort Study. Methods: Retrospective review of medical records was performed to gain more insights into non-HIV comorbidities. Inappropriate prescribing was screened using the Beers criteria, the STOPP/START criteria and the Liverpool drug–drug interactions (DDIs) database. Results: For 175 included individuals, the median age was 78 years (IQR 76–81) and 71% were male. The median number of non-HIV comorbidities was 7 (IQR 5–10). The prevalence of polypharmacy and inappropriate prescribing was 66% and 67%, respectively. Overall, 40% of prescribing issues could have deleterious consequences. Prescribing issues occurred mainly with non-HIV drugs and included: incorrect dosage (26%); lack of indication (21%); prescription omission (drug not prescribed although indicated) (17%); drug not appropriate in elderly individuals (18%) and deleterious DDIs (17%). In the multivariable logistic regression, risk factors for prescribing issues were polypharmacy (OR: 2.5; 95% CI: 1.3–4.7), renal impairment (OR: 2.7; 95% CI: 1.4–5.1), treatment with CNS-active drugs (OR: 2.1; 95% CI: 1.1–3.8) and female sex (OR: 8.3; 95% CI: 2.4–28.1). Conclusions: Polypharmacy and inappropriate prescribing are highly prevalent in elderly people living with HIV. Women are at higher risk than men, partly explained by sex differences in the occurrence of non-HIV comorbidities and medical care. Medication reconciliation and periodic review of prescriptions by experienced physicians could help reduce polypharmacy and inappropriate prescribing in this vulnerable, growing population.